2018
DOI: 10.1007/s00421-018-3937-5
|View full text |Cite
|
Sign up to set email alerts
|

Determining the potential sites of neural adaptation to cross-education: implications for the cross-education of muscle strength

Abstract: Cross-education describes the strength gain in the opposite, untrained limb following a unilateral strength training program. Since its discovery in 1894, several studies now confirm the existence of cross-education in contexts that involve voluntary dynamic contractions, eccentric contraction, electrical stimulation, whole-body vibration and, more recently, following mirror feedback training. Although many aspects of cross-education have been established, the mediating neural mechanisms remain unclear. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 190 publications
0
45
0
Order By: Relevance
“…Nevertheless, there are well-known observations of strength gain in contralateral muscles that have not been exposed to stimulation [ 8 , 20 ] ; this phenomenon is called cross education and may be explained by changes in the nervous system. [ 21 ] The non-detection of this phenomenon in our study may be explained by the short duration of the NMES course (for example, changes in the contralateral limb appeared after 3 weeks of exposure [ 20 ] ).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, there are well-known observations of strength gain in contralateral muscles that have not been exposed to stimulation [ 8 , 20 ] ; this phenomenon is called cross education and may be explained by changes in the nervous system. [ 21 ] The non-detection of this phenomenon in our study may be explained by the short duration of the NMES course (for example, changes in the contralateral limb appeared after 3 weeks of exposure [ 20 ] ).…”
Section: Discussionmentioning
confidence: 97%
“…Questions for the first and second themes emerged from works that identified salient features of the phenomenon and its central and peripheral mechanisms [7,8]. Questions for the third theme were informed by both seminal works [29][30][31][32] and the most recent syntheses of the available evidence [12,15,20]. Questions on the practical aspects and on the clinical outreach (themes 4 and 5) were developed iteratively by the members of the research team (AM, FD, TH) and based on the few clinically oriented reviews that are available [10,13,14,33].…”
Section: Delphi Survey Questions: Contralateral Effects Of Unilateralmentioning
confidence: 99%
“…First reported more than one century ago in the psychomotor literature [4][5][6], this well-known phenomenon continues to attract the attention of both basic and applied scientists who investigate its physiological underpinnings and explore its potential to treat unilateral impairments. The findings of more than 100 individual studies on strength and skill transfer have been summarized in narrative [1,[7][8][9][10][11][12][13], systematic [14,15], and meta-analytic reviews [16][17][18][19][20]. Overall, the aggregate data confirm the robustness of the phenomenon and identifies contexts in which the transfer is particularly consistent among the studies, e.g., voluntary dynamic contractions, eccentric contractions, electrical stimulation, whole-body vibration, and…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Bezerra et al ( 2009 ) observed that VOL + ES would cause additional training effects and greater cross-education compared with VOL training, because it would activate the same neural pathways that are used normally in voluntary exercise, with additional afferent inputs (centrally integrated) provoked by the electrostimulation. The review article by Frazer et al ( 2018 ) linked to neural adaptations as part of the cross-education would reinforce this assumption.…”
mentioning
confidence: 96%